Evaluation and assessments of efficiency calibration and resolution of an alpha spectrometry system using standard sources - Satyanarayan Bramha; S. Chandrasekaran (Radiation Protection and Environment)
Studies and evaluations of the detector characteristics of a high-resolution multichamber alpha spectrometer and its calibration using certified mixed standard sources of 239Pu, 241Am, and 244Cm for measuring alpha-emitting radionuclides dedicated to environmental samples. The efficiency and resolution were evaluated for each potential distance between the source and the detector across all four solid-state ORTEC-ULTRA AS detectors. The results obtained from the characteristics performance of the alpha from the standard alpha sources are described in detail in the paper, and also a case study for the environmental application shows very good recovery using the alpha spectrometer.